PENGEMBANGAN MEDIA PEMBELAJARAN UNGGAH-UNGGUH BAHASA JAWA MELALUI VIDEO ANIMASI UNTUK SISWA KELAS X - Ferra Tri Sastika; Mulyana Mulyana (Universitas Sebelas Maret, 2025)
DEVELOPMENT OF JAVANESE LANGUAGE LEARNING MEDIA THROUGH ANIMATED VIDEOS FOR GRADE X STUDENTSThis research was conducted with 3 (three) objectives, namely: 1) to explain how to make Javanese language learning media using animated video media for class X students; 2) explaining the evaluation of the quality of the Javanese language animated video learning media for class X students; 3) explain the opinion of the Javanese teacher on the quality of learning media of Javanese upload-uploaded animation video for class X students. The method used in this study is the Research and Development (R&D) 4D model which consists of 4 (four) stages, namely: 1) define; 2) designs; 3) develop; and 4) disseminate. The results of this study are: 1) learning media in the form of an animated video uploaded in Javanese which is made through 4 (four) stages; 2) expert lecturers' assessment of the quality of the Javanese upload-uploaded animation video media which gets a percentage of 92%; 3) the Javanese teacher's assessment of the quality of the Javanese language animated video media which gets a percentage of 95%. The results of this study indicate that the Javanese language animated video product for class X is suitable for use as a learning medium in the classroom.